A NARRATIVE RESEARCH APPROACH: ANXIETY IN HEART FAILURE PATIENTS - Kristinawati, Beti; Amirullah, Ahmad Karim; Khasanah, Riska Nurul (International Journal of Psychosocial Rehabilitation, 2020)
The Clinical syndrome that occurs due to decreased cardiac function can lead to anxiety. Excessive and uncontrolled anxiety experienced by patients with heart failure can affect various aspects of life as a whole. The goal of the study was to get an overview of the anxiety experienced by patients with heart failure. The design of narrative research was chosen to gain considerate and formulate anxiety perception by conducting interviews with 17 selected participants with purposive techniques. Thematic analysis was applied to analyze the information obtained from the interviews. The results of the study gained four themes: 1) Fear of death and change of role in the family triggered the onset of anxiety, 2) Physical symptoms occurred when the anxiety arose, 3) The spiritual aspect of it was to reduce the mechanism of anxiety, 4) Emotional support was given to nurses and families to overcome anxiety. Nurses need to have a good understanding of the cause of anxiety, actions to minimize, and attempts to anticipate the emergence of anxiety in patients with heart failure who undergo hospitalization by involving family members. Physical, psycho-social, and spiritual support of nurses and families is needed in the care of heart failure patients.